Evaluation Of Program Implementation Teacher Professional Education In Online Office For Elementary School Teachers - Maryatun Maryatun; lshaq Nuriadin; Suhaenab Supamo (Jurnal Studi Guru dan Pembelajaran, 2023)
The aim of this research is to obtain a description of data regarding the Implementation of the Teacher Professional Education Program (PPG) in Online Positions for Elementary School Teachers which is implemented by FKIP Muhammadiyah University Prof. Dr. Hamka. The in-depth study in this research uses a qualitative perspective which examines the Implementation Teacher Professional Education Program (PPG) in. Method in this research is CIPP, namely context, input, program and product of a program being implemented. The problems studied are related to the background, namely evaluating the background context of PPG UHAMKA and the institutional legal conditions of FKIP UHAMKA in developing human resource experience and infrastructure programs. In evaluating input regarding the readiness of FKIP UHAMKA in implementing PPG, PPG was presented in the position of Primary School Teacher Education (PGSD). Evaluation of learning processes or activities. Then evaluate the products resulting from the Student Performance Test (UKM PPG) in the form of increasing the number of professional teachers who are PGSD certified as evidenced by the resulting pass rate. The 2022 UHAMKA PPG PGSD Product Evaluation Program is very satisfying because the graduation rate is above 84%, this is encouraging news and should be maintained and even improved.